2022
DOI: 10.3389/fimmu.2021.801724
|View full text |Cite
|
Sign up to set email alerts
|

Elevated X-Box Binding Protein1 Splicing and Interleukin-17A Expression Are Associated With Active Generalized Vitiligo in Gujarat Population

Abstract: Vitiligo is an autoimmune skin disorder defined by the destruction of functional epidermal melanocytes. It is a multifactorial and polygenic disorder caused due to oxidative stress, endoplasmic reticulum (ER) stress, and autoimmunity, among other factors. In the present study, we aimed to investigate the association of X-box Binding Protein 1 (XBP1) and Interleukin-17A (IL-17A) polymorphisms and monitor their systemic as well as skin expression levels in vitiligo patients from Gujarat population in India. XBP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(77 reference statements)
0
5
0
1
Order By: Relevance
“…49,50 Patients with Vitiligo have a poor response to ER stress due to a deficiency in their melanocytes that exacerbates inflammation. 51,52 In this study, the effect of LSDV on ER stress-mediated apoptosis and autophagy was not adequately determined. Further research on ER stress-induced apoptosis and degradation may provide new insights into LSDV-infected cellular processes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…49,50 Patients with Vitiligo have a poor response to ER stress due to a deficiency in their melanocytes that exacerbates inflammation. 51,52 In this study, the effect of LSDV on ER stress-mediated apoptosis and autophagy was not adequately determined. Further research on ER stress-induced apoptosis and degradation may provide new insights into LSDV-infected cellular processes.…”
Section: Discussionmentioning
confidence: 89%
“…Keratinization disorders and Keratosis linearis with Ichthyosis Congenita and Sclerosing Keratoderma syndrome (KLICK syndrome) are caused by ER stress that activates UPR signaling and promotes these disorders 49,50 . Patients with Vitiligo have a poor response to ER stress due to a deficiency in their melanocytes that exacerbates inflammation 51,52 . In this study, the effect of LSDV on ER stress‐mediated apoptosis and autophagy was not adequately determined.…”
Section: Discussionmentioning
confidence: 92%
“…Keratinization disorders and Keratosis linearis with Ichthyosis Congenita and Sclerosing Keratoderma syndrome (KLICK syndrome) are caused by ER stress that activates UPR signaling and promotes these disorders (51, 52). Patients with Vitiligo have a poor response to ER stress due to a deficiency in their melanocytes that exacerbates inflammation (53, 54). In this study, the effect of LSDV on ER stress-mediated apoptosis and autophagy was not adequately determined.…”
Section: Discussionmentioning
confidence: 99%
“… 48 In addition, XBP1 increases the expression of immune mediators such as IL-6 and IL-8 as a result of ER stress in melanocytes; 49 meanwhile, recent study revealed that XBP1 is involved in the differentiation of Th17 cells and elevated the level of IL-17A in vitiligo. 50 Activation of the protein kinase R-like endoplasmic reticulum kinase-eukaryotic translation initiation factor 2α (PERK-eIF2α) and inositol-requiring enzyme 1 alpha-X-box-binding protein 1 (IRE1α-XBP1) pathways is of great importance for the production of CXCL16 induced by H 2 O 2 in keratinocytes. 18 Previous studies suggest that HMGB1 promotes the secretion of CXCL16 from keratinocytes by binding to RAGE and activating the endoplasmic reticulum kinase (ERK) and nuclear factor-κB (NF-κB) signaling pathways.…”
Section: Role Of Hmgb1 In the Oxidative Stress-mediated Development O...mentioning
confidence: 99%